The development of learning media “Dual-characters Hand Puppet” to stimulate children's expressive language - Fitriani, Dewi; Hasballah, Jamaliah; Aziz, Umar Bin Abdul; Putri, Diana; Andriansyah, Andriansyah (Universitas Islam Negeri Ar-Raniry, 2022)
Dual-characters hand puppet is the result of combining more than one ordinary hand puppet into a new-designed hand puppet. Dual-characters hand puppet is an innovative learning aid which can be used by teachers or adults with storytelling method which has many benefits especially in stimulating children's expressive language. Expressive language is the ability to ask questions, answer questions, communicate orally, retell what is known, learn pragmatic language, express feelings, ideas, and desires in the form of scribbles. The lack of variety of hand puppet design in stimulating children's expressive language is the basis of this research. This study aims to determine the feasibility of dual-characters hand puppet in stimulating children's expressive language development and to determine children's responses to the use of the media. This study uses an adapted research design from the Borg and Gall Research and Development (R&D) with six (6) stages of research. The results of this study indicate the media feasibility as of 94.5% and content feasibility is 93.7%, both of which are in the “very eligible” category to use. The results of testing the media to measure the child's response received the results as of 87.5% and 85% with the “eligible” category for use.